New optimization methods in Data Mining - Ozogur-Akyuz, S. (2012)
Data mining is a modern area of science dealing with the learning from given data in order to make predictions and estimations. Applications of Data mining can be found in various areas of academical and non academical life. This paper introduces new contributions by continuous optimization as a key technology in data mining. The methods suggested for solution of such important problems as clustering and classification, were recently obtained by the authors in collaboration with members of EURO working group EUROPT.